Effect of lunar landing on its surface, surrounding environment and hardware: A numerical perspective. (February 2022) - Mishra, Sanjeev Kumar; Prasad, K. Durga; Nath, Pranav; Agarwal, Deepak; Kumar, S. Sunil; Bhardwaj, Anil
Abstract: With renewed interest in lunar exploration, soft landing on the Moon has gained prominence in the recent past. Most of the modern-day landers use throttleable thrusters to make a safe and soft landing. However, the jet plume produced by the exhaust of these thrusters creates disturbance on the lunar surface which first leads to surface disturbance and subsequently create damage by the ejected particles to the surroundings and hardware present in the vicinity of the landing site. Understanding this disturbance and assessing the damage is significant both for science as well as mission safety, particularly, keeping in view the plans for ISRU (In-situ Resource Utilisation)/Lunar outpost activities in future. In the present study, an attempt is made to assess the extent of damage caused to the surrounding hardware left by an earlier landing in the vicinity of the landing site. A damage model in conjunction with plume dynamics and its interaction with the lunar surface is used to arrive at the estimates. A Direct Simulation Monte Carlo (DSMC) solver is used for the analysis of plume dynamics and gaseous interactions of the plume with the in-situ lunar soil. The output of the DSMC solver is employed to quantify the ejecta parameters such as eject velocity, mass flux rate, ejecta kinematics, which are used to estimate the expected damage to a lunar outpost or hardware present in its vicinity. Estimates are made on the total amount of damage (defined as the amount of lunar regolith ejected from the surface in to the surrounding environment) at different stages of landing, ejecta kinematics and overall volume of pit/dent formed on the surface of surrounding hardware due to the high velocity ejecta particles. The study considers a typical test case using a landing trajectory of a small class lander mission for these calculations and presents a picture of surface disturbance, ejecta profile and damage that could happen to the surroundings up to few 100s of meters. An ejecta amount of 7.5 ​kg beneath the lander and a damage of 1500 ​mm 3 to the surrounding hardware (situated at 100m from landing site) is estimated from the configuration considered in the present study. Although the disturbance and damage caused due to small class landers seems to be minimal, large class landers and landing in a close vicinity of an earlier landing would cause significant threat to the existing hardware which needs to be mitigated for all future lunar ISRU/outpost activities. Highlights: Extent of damage caused to the lunar surface and its surroundings due to a lunar landing is discussed. Significant for both science as well as mission safety, keeping in view the proximity landing demanded by future ISRU/Lunar outpost activities. DSMC code is used to evaluate the plume dynamics and its interaction with the lunar soil. Kinematics of the ejected lunar dust and its impact on a pre-existing hardware in the vicinity is predicted. Evaluation and recommendations for materials to be used in future spacecraft structures to mitigate the problem is provided.